Harassment from the Perspective of the Current Romanian Criminal Code - Drăgan Alin Teodorus (Journal of Legal Studies)
The legislator of the Criminal Code resorted to the criminalization of this deed in response to cases that occurred in everyday reality, in which various persons, especially women, are waited for and followed in the street or other public spaces or are badgered via phone calls or messages, all of which are done in such a way as to create a state of fear for the person in question.